My family for the war - Voorhoeve, Anne C. (Dial Books, 2012)
Ten-year-old Franziska Mangold escapes Nazi Germany on the kindertransport she boards in Berlin, and when she arrives in London, she takes on the name Frances and struggles with her identity as she pieces together a new life without her family.